Antioxidant Effects of Apocynum venetum Tea Extracts on d-Galactose-Induced Aging Model in Mice - Chong Li; Fang Tan; Jianjun Yang; Yue Yang; Yuting Gou; Shuting Li; Xin Zhao (MDPI AG, 2019)
As a traditional Chinese medicinal drink, Apocynum venetum, a local tea from Xinjiang, China, is favored for its rich flavor and biological functionality. This study looked at aging mice induced by d-galactose to determine the in vivo anti-aging effect of Apocynum venetum tea extracts (AVTEs) and its bioactive components. We evaluated the weight of major organs (via organ index) and pathological changes in the liver. We also detailed the effects of AVTE (250 mg/kg in the low dose group, 500 mg/kg in the high dose group) on biochemical parameters (malondialdehyde, superoxide dismutase, glutathione, glutathione peroxidase, catalase, total antioxidant capacity, and nitric oxide) and cytokines (IL-6, IL-12, TNF-α and IL-1β) in the serum of aging mice. We investigated the anti-aging effects of AVTE in d-galactose-induced aging mice via quantitative real-time reverse transcription-polymerase chain reaction (RT-qPCR) assay. In addition, we analyzed the biological components of AVTEs by high performance liquid chromatography (HPLC). The results were remarkable, suggesting that AVTE significantly improved d-galactose-induced aging mice, with the high dose group showing the best results among other groups. ATVE can effectively alleviate hepatocyte edema, as well as inflammatory cell infiltration and injury in mice, induce a protective effect via up-regulation of glutathione (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT) antioxidant related factors, and play an important role in the up-regulation of anti-inflammatory factors (IL-10) and the down-regulation of pro-inflammatory factors (IL-6, TNF-α and IL-1β). At the same time, HPLC analysis showed that AVTEs contain neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, rutin, isoquercitrin, isochlorogenic acid B, isochlorogenic acid A, astragalin, isochlorogenic acid C, rosmarinic acid, and trans-cinnamic acid. Thus, AVTE appears to be an effectively functional drink due to its rich functional components and anti-aging activities.